2009
DOI: 10.1007/s10725-009-9393-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of biochemical and morphophysiological changes during zygotic embryogenesis in Acca sellowiana (Berg.) Burr.

Abstract: Acca sellowiana (Berg.) Burr. is a native Myrtaceae from southern Brazil and Uruguay, now the subject of a domestication and breeding program. Biotechnological tools have been used to assist in this program. The establishment of a reliable protocol of somatic embryogenesis has been pursued, with a view to capturing and fixing genetic gains. The rationale behind this work relies on the fact that deepening comprehension of the general metabolism of zygotic embryogenesis may certainly improve the protocol for som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 65 publications
2
6
1
Order By: Relevance
“…Amino acid levels, as determined in the present study, are coincident with patterns observed in zygotic embryos at the same developmental stages (Cangahuala-Inocente et al 2009a), but at relatively lower levels. However, it should be stressed that in the case of zygotic embryos the presence of teguments and endosperm tissues may have affected the accumulation patterns of these compounds.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Amino acid levels, as determined in the present study, are coincident with patterns observed in zygotic embryos at the same developmental stages (Cangahuala-Inocente et al 2009a), but at relatively lower levels. However, it should be stressed that in the case of zygotic embryos the presence of teguments and endosperm tissues may have affected the accumulation patterns of these compounds.…”
Section: Resultssupporting
confidence: 86%
“…During A. sellowiana zygotic embryogenesis, in the collecting times corresponding to the evaluated developmental stages, the predominant amino acids were asparagine and glutamine (Cangahuala-Inocente et al 2009a). However, in the present work, the predominant amino acids in A. sellowiana somatic embryos were arginine and asparagine.…”
Section: Resultscontrasting
confidence: 63%
See 3 more Smart Citations